2005
DOI: 10.1159/000091446
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Hepatitis C Virus-Associated Intrahepatic Cholangiocarcinoma

Abstract: Background: Although hepatitis C virus (HCV) infection is a possible pathogenetic factor for intrahepatic cholangiocarcinoma (ICC), clinicopathologic features of ICC patients with HCV infection remain unclear. Patients and Methods: Of 50 patients with ICC treated, 19 were infected with HCV (HCV-positive group) and 38 underwent surgical treatment. Clinicopathologic features and postoperative outcome were compared between patients with and without HCV infection. Results: In 15 patients in the HCV-positive group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
(22 reference statements)
1
28
0
Order By: Relevance
“…Previous reports showed a relationship between ICC and hepatitis C viral infection [25,26]; furthermore, the carcinogenesis of ICC may be caused by hepatitis viral infection [27]. In such a situation, hepatocytes may alter a cholangiocarcinoma by stimulating chronic inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports showed a relationship between ICC and hepatitis C viral infection [25,26]; furthermore, the carcinogenesis of ICC may be caused by hepatitis viral infection [27]. In such a situation, hepatocytes may alter a cholangiocarcinoma by stimulating chronic inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several reports have suggested that infection with hepatitis B or C virus is a possible etiological factor for cholangiocarcinoma. 8,9,[16][17][18] Viral hepatitis-associated cholangiocarcinomas have some clinical features in common with hepatocellular carcinoma. They tend to occur at an earlier age, affect men more frequently, are more likely to cause elevated serum a-fetoprotein levels, and less likely to cause elevated serum CA19-9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, several studies from Japan, Korea, China, and Taiwan indicate that viral hepatitis B and C are statistically related to intrahepatic cholangiocarcinoma. 8,9,[16][17][18] Compared with seronegative intrahepatic cholangiocarcinoma patients, hepatitis B-related intrahepatic cholangiocarcinoma patients tend to be younger and are more frequently male, have higher abnormal aminotransferase and a-fetoprotein levels, and lower abnormal serum carbohydrate antigen 19-9 (CA19-9) levels. 17 Taken together, these findings suggest that hepatitis virus-associated intrahepatic cholangiocarcinoma and hepatocellular carcinoma share common disease processes for carcinogenesis.…”
mentioning
confidence: 99%
“…The relationship between ICC and hepatitis viral infection closely related such a type of ICC, in which cancer cell origin or stem cells would be caused by chronic hepatitis [37][38][39][40]. Hepatocyte-originated tumors might be expected to show early enhancement, as seen in HCC [33,35].…”
Section: Nanashima Et Al Page 10mentioning
confidence: 99%